Towards efficient terpenoid biosynthesis: manipulating IPP and DMAPP supply - Qin Wang; Shu Quan; Han Xiao (Bioresources and Bioprocessing, 2019)
Abstract Terpenoids are a group of largest natural products with important biological functions, and their efficient biosynthesis is of particular importance to both academia and industry. As the building blocks for terpenoid biosynthesis, a suitable supply of isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP) is extremely crucial for efficient terpenoid biosynthesis. With this focus, we first introduce biosynthetic pathways of IPP and DMAPP, and then summarize the current strategies adopted for manipulating IPP and DMAPP supply. At last, how to further manage IPP and DMAPP supply to improve terpenoid biosynthesis is also proposed.